2015
DOI: 10.1093/nar/gkv889
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a cAMP responsive transcription factor, Cmr (Rv1675c), in TB complex mycobacteria reveals overlap with the DosR (DevR) dormancy regulon

Abstract: Mycobacterium tuberculosis (Mtb) Cmr (Rv1675c) is a CRP/FNR family transcription factor known to be responsive to cAMP levels and during macrophage infections. However, Cmr's DNA binding properties, cellular targets and overall role in tuberculosis (TB) complex bacteria have not been characterized. In this study, we used experimental and computational approaches to characterize Cmr's DNA binding properties and identify a putative regulon. Cmr binds a 16-bp palindromic site that includes four highly conserved n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 83 publications
2
51
0
Order By: Relevance
“…This suggests that Cmr-mediated gene regulation is complex and its influence over M. tuberculosis stress responses extends beyond de-repression of the DosR-regulon, as indicated by the ChIP-seq data reported by Ranganathan et al. for M. bovis BCG (13). Moreover, Cmr-mediated gene expression could be further complicated by its capacity to respond to both oxidation and nitrosation.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that Cmr-mediated gene regulation is complex and its influence over M. tuberculosis stress responses extends beyond de-repression of the DosR-regulon, as indicated by the ChIP-seq data reported by Ranganathan et al. for M. bovis BCG (13). Moreover, Cmr-mediated gene expression could be further complicated by its capacity to respond to both oxidation and nitrosation.…”
Section: Discussionmentioning
confidence: 99%
“…AbmR's putative operator contains a biochemically validated Cmr-binding site (Gazdik et al, 2009) and a predicted CRP Mt -binding site (Arnvig et al, 2011). While neither TF was found within the Rv1264-mcr11-abmR region in recent ChIP-seq studies (Kahramanoglou et al, 2014, Knapp et al, 2015Ranganathan et al, 2016), regulation of abmR by both Cmr and CRP Mt have been reported (Gazdik et al, 2009;Arnvig et al, 2011;Kahramanoglou et al, 2014;Knapp et al, 2015). The possibility that AbmR, Cmr and/or CRP Mt engage in competitive or cooperative DNA binding in this region warrants further investigation, as does the potential for indirect regulation by AbmR of gene targets downstream of Mcr11.…”
Section: Gene Regulatory Functions Of Abmr and Regulatory Networkmentioning
confidence: 99%
“…The universal second messenger molecule 3′, 5′ cyclic adenosine monophosphate (cAMP) is a global regulator of gene expression within Mtb, while secreted cAMP modulates Mtb's interactions with host macrophages (Lowrie et al, 1979;Agarwal et al, 2009;Bai et al, 2009;Nambi et al, 2013;Kahramanoglou et al, 2014;Knapp et al, 2015;Ranganathan et al, 2016;Johnson et al, 2017). cAMP levels affect the gene regulatory activities of two virulence-associated CRP/FNR family transcription factors in Mtb, Cmr and CRP Mt (Bai et al, 2005;Rickman et al, 2005;Kahramanoglou et al, 2014;Ranganathan et al, 2016). We previously identified gene of unknown function Rv1265 as a direct regulatory target of Cmr (Gazdik and McDonough, 2005;Ranganathan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioinformatic analyses indicate that most of these ACs contain different combinations of functional protein domains, suggesting a capacity to integrate multiple activities with cAMP signaling in Mtb (McCue et al ., ). cAMP‐responsive transcription factors Crp MT (Rv3676) and Cmr (Rv1675c) in Mtb regulate gene expression (Rickman et al ., ; Gazdik et al ., ; Stapleton et al ., 2010; 2012; Knapp et al ., ; Ranganathan et al ., ) to control metabolism, pathogenicity, dormancy and stress responses (Rickman et al ., ; Gazdik et al ., ; Stapleton et al ., ; Xu et al ., ; Pelly et al ., ; Hayden et al ., ; Nambi et al ., ; Choudhary et al ., ; Knapp et al ., ; Ranganathan et al ., ). In addition, elevated cAMP levels in Mtb can stimulate activity of the lysine acetyl‐transferase MtPat (Rv0998), which modulates the function of key metabolic enzymes via post‐translational modifications (Xu et al ., ; Hayden et al ., ; Nambi et al ., ).…”
Section: Introductionmentioning
confidence: 99%